UTILIZAÇÃO DE INDICADORES DE EMISSÕES ATMOSFÉRICAS COMO FERRAMENTA DE DECISÃO EM PROJETOS DE UNIDADES MARÍTIMAS DE PRODUÇÃO DE ÓLEO E GÁS - Pimenta, Gladston Francisco P. (2005)
This essay presents the study of utilization of environmental indicators in oil and gas offshore production unit design. The indicators in question represent the tax of greenhouse gas emissions per produced equivalent oil (I1) and the tax of greenhouse gas emissions per energy consumption with fuels (I2). This essay describes the problem of global warming, in order to point out the weightiness of GEE reduction actions. This essay also describes international legislation and agreements concerning GEE emission. In the end is presented the results of the evaluation of the proposed indicators for 31 existing offshore units. The presented values of emissions, oil and gas production, energy and fuel consumption of the units were multiplied by factors and do not match with the real values. The proposal of this methodology is to turn available a comparison between the values of GEE emissions obtained in the project and the environmental indicators I1 and I2, to be used as an environmental matter during an offshore unit design, to be considered with the economic decisions in the choice of equipment and systems.